2017
DOI: 10.1111/hequ.12119
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Chinese University Undergraduates’ Global Competence: Effects of Internationalisation at Home and Motivation

Abstract: Global competence is categorised into three dimensions: knowledge, skills/experience and attitudes. This study aims to investigate the global competence discrepancies of Chinese undergraduates in universities and regions of different development levels, as well as the effects of internationalisation efforts at home and students’ motivation on global competence. To this end, 2,695 students within nine universities (three 985 project universities, three 211 project universities and three provincial universities)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Mass media [8] Mass migration [8] Time zone differences [8] Contact with foreigners [9] Family influences…”
Section: Student Educational Environment and Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass media [8] Mass migration [8] Time zone differences [8] Contact with foreigners [9] Family influences…”
Section: Student Educational Environment and Experiencesmentioning
confidence: 99%
“…First, students' global competence is enhanced by their international learning environment and experiences [8]. Studying abroad is considered a primary way for students to enhance their global competence by recognizing diversity and engaging more in intercultural communication [9]. Through surveys of college students in a U.S. university and a Korean university, researchers found that cross-and inter-cultural projects also had a significant positive impact on the communication skills and knowledge of the participants [8].…”
Section: Student Educational Environment and Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversas são as formas pelas quais as instituições de ensino superior podem se internacionalizar (GUO; GUO, 2017;MENG, ZHU, CAO, 2017;BEDENLIER;KONDAKCI;ZAWACKI-RICHTER, 2018;WIHLBORG;ROBSON, 2018), e de acordo com Alsharari (2019), as oportunidades em acelerar a internacionalização nas instituições de ensino superior incluem a melhoria geral na qualidade da educação, difusão de tecnologia e criação de uma força de trabalho competente globalmente.…”
Section: Internacionalização Das Instituições De Ensino Superiorunclassified
“…This study analyses the support services that students receive for the development and acknowledgement of mobility related knowledge, skills and attitudes. Boyatzis (1982) defines "competence" as the underlying characteristics of the individual causally related to an effective or superior performance in a professional activity; where the individual characteristics are commonly classified in the following three dimensions (Meng et al, 2017): (i) knowledge or the "cognitive" dimension of competence. It refers to all the topics and issues individuals know or need to know to perform a specific task; (ii) skills, the "practical" or applied dimension of competence, which refers to what individuals are able to do or what they need to be able to do to perform a specific task, and (iii) the attitudes (and values) that individuals must espouse in order to perform a specific task effectively.…”
Section: Introductionmentioning
confidence: 99%